Influence of rhenium on γ′-strengthened cobalt-base superalloys - Kolb, Markus; Zenk, Christopher; Kirzinger, Anna; Povstugar, Ivan; Raabe, Dierk; Neumeier, Steffen; Göken, Mathias (Journal of Materials Research, 2017)
The element Re is known to be a very potent strengthener concerning the creep properties of Ni-base superalloys. In this paper the influence of Re on the properties of new gamma'-strengthened Co-base superalloys is addressed. Atom probe tomography reveals that Re partitions preferentially to the gamma phase, but not as pronounced as in ni-base superalloys. Nanoindentation and micro-pillar compression tests of the gamma' phase indicate an increase of the hardness and the critical resolved shear stress caused by a considerable concentration of Re in the gamma' phase. Creep investigations show that the positive effect of Re is by far not as pronounced as in Ni-base superalloys. Several effects, which can contribute to this behavior, such as the lower Re concentration in gamma and hence a slightly reduced effective diffusion coefficient, a smaller diffusion barrier of Re in Cocompared to Ni, a slightly lower lattice misfit and gamma' volume fraction of the Re-containing alloy, are discussed.

Local Mechanical Properties at the Dendrite Scale of Ni-Based Superalloys Studied by Advanced High Temperature Indentation Creep and Micropillar Compression Tests - Haußmann, Lukas; Neumeier, Steffen; Kolb, Markus; Ast, Johannes; Mohanty, Gaurav; Michler, Johann; Göken, Mathias (Minerals, Metals and Materials Series, 2020)
Chemical inhomogenities due to dendritic solidification of Ni-based superalloys result in different local microstructures with varying mechanical properties. New indentation creep test methods allow probing of the local creep properties at the dendrite scale at high temperatures. The as-cast single crystalline Ni-based superalloy ERBO1A (a derivative alloy of CMSX–4) was investigated and electron-probe microanalysis (EPMA) measurements revealed strong segregation of, e.g., Re and W in the dendritic region and, e.g., Ta in the interdendritic region. Indentation creep experiments at 750 °C and micropillar compression tests at 785 °C were conducted in both regions, and a higher creep strength was found in the dendritic region compared to the interdendritic region. Theoretical models for solid solution hardening as well as γ′ precipitation hardening confirm these results, since they predict a higher strength in the dendritic region than in the interdendritic region. Compared with the fully heat treated state, a smaller difference in the local mechanical properties or even a reverse strength ratio of the dendritic and interdendritic region can be expected.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dendritic segregations; Indentation creep; Micropillar compression; Ni-based superalloy

Local mechanical properties of the (β0+ω0) composite in multiphase titanium aluminides studied with nanoindentation at room and high temperatures - Kolb, Markus; Wheeler, J. M.; Mathur, H. N.; Neumeier, Steffen; Korte-Kerzel, Sandra; Pyczak, Florian; Michler, J.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2016)
WW1::1067
Keywords: High Temperature

Mechanical behaviour of novel sintered Co-Al-W alloys at high temperatures - Cartón-Cordero, Marta; Campos, Mónica; Freund, Lisa; Kolb, Markus; Neumeier, Steffen; Göken, Mathias; Torralba, José M. (World Powder Metallurgy 2016 Congress and Exhibition, World PM 2016, 2016)
Keywords: Superalloys; Co-Al-W alloys; Mechanical properties; Mechanical milling; PM route; Nanoindentation

Microstructure and compression strength of Co-based superalloys hardened by γ′ and carbide precipitation - Carton-Cordero, Marta; Campos, Monica; Freund, Lisa; Kolb, Markus; Neumeier, Steffen; Göken, Mathias; Torralba, José M. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2018)
A Co-based superalloy, Co-9Al-9W (at%), was processed by mechanical alloying by high-energy milling of elemental powders and consolidated by field assisted hot pressing (FAHP). The milled powder particles mainly consist of undissolved bcc-W as well as WC and an Al and W rich fcc-gamma Co solid solution. After consolidation and heat treatment a fine grained microstructure with a high fraction of carbides and a gamma/gamma' microstructure was obtained. The compressive yield strength at room temperature was found to be 45% higher than that of previously reported results for Co-based superalloys. A similar level of strength was found at 700 degrees C. These extraordinary properties can be explained due to the multitude of hardening mechanisms that sintered Co-based superalloys possess: gamma' precipitation, carbide formation and the ultra-fine se-grain size promoted by the fast consolidation technique.
Keywords: Co-Al-W superalloys; PM route; Mechanical properties; Nanoindentation; Mechanical milling

New flat-punch indentation creep testing approach for characterizing the local creep properties at high temperatures - Matschkal, Dorothea; Kolb, Markus; Neumeier, Steffen; Gao, S.; Hartmaier, A.; Durst, K.; Göken, Mathias (Materials & Design, 2019)
An indentation creep testing approach has been developed which allows measuring creep properties at high temperatures. In contrast to existing indentation or impression creep experiments, the approach described here allows to achieve a quite high spatial resolution, as flat punch indenters with a diameter of only 20 μm are used. First indentation creep tests have been performed on single crystalline nickel and nickel binary solid solution alloys with Re, Ta or W as alloying elements, respectively. The indentation creep tests have been carried out at a temperature of 650 °C and stress levels in the range of 85 to 400 MPa. Using crystal plasticity finite element modeling, the indentation creep response is converted into equivalent uniaxial creep properties. It is shown that the conversion parameters, evaluated for differently oriented single crystals, can be chosen independently of the creep rate exponent in the power law creep regime. It is found that the indentation creep results agree well with conventional uniaxial creep tests. Furthermore, the results show that Ta is the most effective solid solution strengthener of all tested solid-solution strengtheners at 650 °C because of the large atomic size mismatch, followed by W and Re.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Creep testing; Indentation creep testing; Indentation testing; Ni-alloys; Solid solution strengthening

On the grain boundary strengthening effect of boron in γ/γ′ Cobalt-base superalloys - Kolb, Markus; Freund, Lisa; Fischer, Florian; Povstugar, Ivan; Makineni, Surendra Kumar; Gault, Baptiste; Raabe, Dierk; Müller, Julian; Spiecker, Erdmann; Neumeier, Steffen; Göken, Mathias (Acta Materialia, 2018)
Boron is an essential solute element for improving the grain boundary strength in several high temperature metallic alloys especially in Ni- and Co-base superalloys although the detailed strengthening mechanisms are still not well understood. In superalloys, boron leads to the formation of borides and precipitate depleted zones around the grain boundaries and alters the bond strength among the grains directly. In this paper, we explore in detail the role of the boron content in ternary γ/γ′ Co-9Al-9W alloys. Local as well as bulk mechanical properties were evaluated using nanoindentation and compression testing and correlated to near-atomic scale microstructure and compositions obtained from electron microscopy and atom probe tomography. The alloy variant with low B content (0.005 at.% B) reveals an increase in yield strength at room temperature and 600 °C and atom probe tomography investigations show that solute B segregates to the grain boundaries. However, in the bulk B exclusively partitions to the γ′ phase. Additionally, the γ′/γ′ grain boundaries are depleted in W and Al with the concentration locally shifted towards the γ composition forming a very thin γ layer at the γ′/γ′ grain boundaries, which supports dislocation mobility in the γ′/γ′ grain boundary region during deformation. Higher content of B (0.04 at.% B) promotes formation of W-rich borides at the grain boundaries that leads to undesirable precipitate depleted zones adjacent to these borides that decrease the strength of the alloy drastically. However, it was also found that a subsequent annealing heat treatment eliminates these detrimental zones by re-precipitating γ′ and thus elevating the strength of the alloy. This result shows that, if a precipitate depleted zone can be avoided, B significantly improves the mechanical properties of polycrystalline Co-base superalloys by strengthening the γ′ phase and by improving grain boundary cohesion.
Keywords: Cobalt-base superalloys; Borides; Grain boundary; Atom probe tomography (APT); Nanoindentation

The role of the base element in γ′ strengthened cobalt/nickel-base superalloys - Zenk, Christopher; Neumeier, Steffen; Kolb, Markus; Volz, Nicklas; Fries, S. G.; Dolotko, O.; Povstugar, I.; Raabe, D.; Göken, Mathias (13th International Symposium on Superalloys, SUPERALLOYS 2016, 2016)
Keywords: Creep; Lattice misfit; Atom probe tomography; Co-base superalloys; Partitioning behavior